Liposome encapsulated clodronate mediated elimination of pathogenic macrophages and microglia: A promising pharmacological regime to defuse cytokine storm in COVID-19 - Sowbarnika Ravichandran; Nivethitha Manickam; Mahesh Kandasamy (Elsevier, 2022)
The emergence of new SARS-CoV-2 variants continues to pose an enormous public health concern. The SARS-CoV-2 infection disrupted host immune response accounting for cytokine storm has been linked to multiorgan failure and mortality in a significant portion of positive cases. Abruptly activated macrophages have been identified as the key pathogenic determinant of cytokine storm in COVID-19. Besides, reactive microglia have been known to discharge a surplus amount of proinflammatory factors leading to neuropathogenic events in the brains of SARS-CoV-2 infected individuals. Considering the fact, depletion of activated macrophages and microglia could be proposed to eradicate the life-threatening cytokine storm in COVID-19. Clodronate, a non-nitrogenous bisphosphonate drug has been identified as a potent macrophage and microglial depleting agent. While recent advancement in the field of liposome encapsulation technology offers the most promising biological tool for drug delivery, liposome encapsulated clodronate has been reported to effectively target and induce prominent phagocytic cell death in activated macrophages and microglia compared to free clodronate molecules. Thus, in this review article, we emphasize that depletion of activated macrophages and microglial cells by administration of liposome encapsulated clodronate can be a potential therapeutic strategy to diminish the pathogenic cytokine storm and alleviate multiorgan failure in COVID-19. Moreover, recently developed COVID-19 vaccines appear to render the chronic activation of macrophages accounting for immunological dysregulation in some cases. Therefore, the use of liposome encapsulated clodronate can also be extended to the clinical management of unforeseen immunogenic reactions resulting from activated macrophages associated adverse effects of COVID-19 vaccines.